Willingness to Bear Economic Costs in the Fight Against the COVID-19 Pandemic - Sokolowska, Joanna; Zaleskiewicz, Tomasz (Frontiers in Psychology, 2020)
The COVID-19 pandemic has created a situation in which people have to choose between economic and health values. This raises the question of what psychological mechanisms determine people’s willingness to bear economic costs to protect health? To answer this question, we examined whether such willingness is better described by compensatory or lexicographic models of decision making in situations involving risk or uncertainty. We compared decisions regarding COVID-19 and occupational diseases to establish a pandemic-independent baseline and to determine whether the mechanisms behind the trade-offs are the same in both cases. Additionally, we tested whether people’s willingness to accept economic costs is related to psychological factors such as fear, feeling of control, declared knowledge about the COVID-19 pandemic, predictions concerning the expected length of the pandemic, and perceived effectiveness of actions taken to fight the coronavirus. In total, 354 Polish participants from Prolific Academic took part in this study. The results were consistent with the view that decisions are made primarily to protect sacred values and are therefore not based on compensatory models. In line with this view, participants were sensitive neither to the risk vs. uncertainty manipulation nor to the perceived effectiveness of the lockdown. Instead, their behavior was congruent with lexicographic models in which the protection of health and in particular the fight against the COVID-19 pandemic appeared to be the most important dimension, and the single criterion to be used in decision making.